ANALISA JUMLAH KROMOSOM IKAN MAS KOKI (Carrasius auratus) TETRAPLOID YANG DIHASILKAN DENGAN METODE KEJUTAN PANAS - Rustidja Rustidja (Universitas Gadjah Mada, 2004)
The objectives of research was to analyses the chromosome numbers of tetraploid goldfish (Carassius auratus) produced by heat shocking method. The tetraploidy was carried out 29 minutes after fertilization of eggs by heat shocking for 1.5 minutes at 400C.The chromosome number was analyzed with the modus of chromosomes.The results indicated that 1) the diploid control of goldfish has 100.28% + 0.0982 chromosom with modus numbers of 100, and the tetraploid goldfish has 199.94 + 0.982 chromosomes with number of modus at 200. 2) The effectiveness of the heat shocking method in goldfish for tetraploidy was 46.60%.The hatching rate of diploid control (65.068% + 0.52%) was significantly diferent with that of tetraploid fish (24.53% + 1.649%). In addition, the survival rate of diploid controls (86.875% + 6.287). was significantly different with that of tetraploid goldfish (34.274% + 19.289%) and the specific growth rates of diploid controls (5,104 + 0,074) was not significantly diferent that of with tetraploid fish (3.982 + 0.011).